Timecop : the Berlin decision - Boyum, Stephen (Universal City, Calif : Universal, 2003)
Ryan Chang is a maverick Timecop who's assigned to prevent criminals from traveling to the past and altering the future. The clock is ticking and Ryan must track down the evil mastermind Branson who's bent on using history as the ultimate weapon.
English dialogue, French or Spanish subtitles; Closed-captioned.
Based on the comic series created by Mike Richardson and Mark Verheiden.
Special features: The making-of 'Timecop 2: The Berlin decision'; between takes: a look at life on the 'Timecop' set with actress Tava Smiley; recommendations.
Keywords: Time travel -- Drama; Police -- Drama; Criminal behavior -- Drama